Basal cell nevoid carcinoma syndrome: A review - Marinho, Sandra Aparecida; da Silva, Heglayne Pereira Vital (Seven Editora, 2023)
Basal cell nevoid carcinoma syndrome (BCNCS) is a rare autosomal dominant genetic syndrome that is predisposed to cancer. It is characterized by the presence of multiple basal cell carcinomas (BCCs) on the skin, as well as numerous maxillary odontogenic keratocyst (QTOs), palmoplantar punctate depressions (pits), skeletal abnormalities, and other developmental defects. The genetic basis of this syndrome lies in causal mutations in the PTCH1 gene, a tumor suppressor gene located on chromosome 9. The present study aimed to review recent literature concerning SCNBC, addressing aspects such as clinical manifestations, diagnostic criteria, genetic etiology, and molecular tests used. A total of 88 articles were included, most of which were clinical cases. Among the clinical manifestations, QTOs were the most frequently mentioned major diagnostic criteria, followed by calcification of the cerebral sickle. Ocular anomalies, on the other hand, were the alterations belonging to the most prevalent minor criteria. A total of 18 clinical cases underwent molecular testing for mutations in the PTCH1 gene. The most used methods were genetic sequencing and the mutations frequently found were frameshift and nonsense mutation, which occurred in exons 2, 3, 6, 8, 11,  12, 18, and 21.  Despite the existence of several mutations in the PTCH1  gene that are attributable to the etiology of SCNBC, the performance of diagnostic molecular tests were not performed in many of the studies analyzed, and even those that did not identify a correlation with the patient's phenotype or prognosis, and these are indicated only in some particular cases.DOI:https://doi.org/10.56238/alookdevelopv1-086